Genome Wide Association Study of Neuropathic Ocular Pain - Jaxon J. Huang, BHSc; Daniel A. Rodriguez, MD, PhD; Susan H. Slifer, MSc; Eden R. Martin, PhD; Roy C. Levitt, MD; Anat Galor, MD, MSPH (Ophthalmology Science, 2024)
Purpose: To conduct a genome-wide association study (GWAS) of individuals with neuropathic ocular pain (NOP) symptoms to identify genomic variants that may predispose to NOP development. Design: Prospective study of individuals with NOP. Participants: Three hundred twenty-nine patients recruited from the Miami Veterans Affairs eye clinic. Methods: The Neuropathic Pain Symptom Inventory modified for the eye (NPSI-Eye) was completed to calculate a NPSI-Eye-Sub-Score (summed ratings of burning and wind sensitivity) as an indicator of NOP severity. A GWAS was performed for the NPSI-Eye-Sub-Score with a significance threshold of P < 5 × 10−8. A gene-based analysis was performed using the multimarker analysis of genomic annotation software (in the functional mapping and annotation of GWAS online platform). The 13 865 778 single nucleotide polymorphisms (SNPs) from our GWAS analysis were mapped to 10 834 protein coding genes, and significant genes were run through gene set enrichment analysis. Main Outcome Measures: Identification of SNPs and protein products that may be associated with the development of NOP. Results: One hundred seventy-one SNPs reached a threshold of P < 10−5, of which 10 SNPs reached the suggestive level of significance of P < 5 × 10−7 and 1 SNP met our genome-wide significance threshold of P < 5 × 10−8. This lead SNP, rs140293404 (P = 1.23 × 10−8), is an intronic variant found within gene ENSG00000287251 coding for transcript ENST00000662732.1. Rs140293404 is in linkage disequilibrium with exon variant rs7926353 (r2 > 0.8) within ENSG00000279046 coding for transcript ENST00000624288.1. The most significant genes from gene-based tests were matrix metalloproteinase-19 (MMP19) (P = 1.12 × 10−5), zinc finger RNA-binding motif and serine/arginine rich-1 (ZRSR1) (P = 1.48 × 10−4), CTC-487M23.8 (P = 1.79 × 10−4), receptor expression-enhancing protein-5 (REEP5) (P = 2.36 × 10−4), and signal recognition particle-19 (SRP19) (P = 2.56 × 10−4). From gene set enrichment analysis, the sensory perception (false discovery rate = 6.57 × 10−3) and olfactory signaling (false discovery rate = 1.63 × 10−2) pathways were enriched with the most significant genes. Conclusions: Our GWAS revealed genes with protein products that may impact sensory perception, lending biological plausibility to a role for SNPs identified by our GWAS in the development of NOP. A better understanding of the biological relevance of these genes and pathways in the pathophysiology associated with NOP may facilitate future novel mechanism-based treatments. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.